Survivin is Highly Expressed and Promotes Cell Survival in Malignant Peritoneal Mesothelioma - Nadia Zaffaroni; Aurora Costa; Marzia Pennati; Cinzia De Marco; Emanuela Affini; Maria Madeo; Roberta Erdas; Antonello Cabras; Shigeki Kusamura; Dario Baratti; Marcello Deraco; Maria Grazia Daidone (Cellular Oncology)
Background: The biology of malignant peritoneal mesothelioma (MPM) is largely unknown. In the present study, we assessed the expression of survivin and other members of the inhibitors of apoptosis proteins (IAP) family (IAP-1, IAP-2 and X-IAP) in a series of 32 MPM surgical specimens and investigated the effects of survivin knockdown in an established MPM cell line. Methods: Expression of different IAPs was measured by immunohistochemistry. MPM cells were transfected with a small-interfering RNA (siRNA) targeting survivin mRNA and analyzed for survivin expression, growth rate, and ability to undergo spontaneous and drug (cisplatin, doxorubicin)-induced apoptosis. Results: Survivin expression was observed in 29 (91%) surgical MPM specimens, whereas the positivity rate for the other IAPs ranged from 69% to 100%. Transfection of MPM cells with the survivin siRNA induced a marked inhibition of survivin protein expression, a time-dependent decline in cell growth and an enhanced rate of spontaneous and drug-induced apoptosis, with a concomitant increase in the catalytic activity of caspase-9. Conclusion: Our results show for the first time that survivin, as well as other IAPs, is largely expressed in clinical MPMs and suggest that strategies aimed at down-regulating survivin may provide a novel approach for the treatment of the malignancy.